Five-year clinical outcomes and costs of burn injuries: a portrait of burn care in Quebec, Canada - Naomi Hope Chouinard; Chanel Beaudoin Cloutier; Isabelle Xu; Sue-Ling Chang; Alice Dragomir; Lucie Germain; Eduardo Gus; Lynne Moore; Véronique J. Moulin; Andrée-Anne Roy; Jason Robert Guertin (Orphanet Journal of Rare Diseases, 2026)
Abstract Background Although rare, burn injuries are among the most complex trauma cases. Partial deep dermal and full thickness burns are considered as a rare disease. There is limited population-level evidence on post-discharge trajectories following a burn injury, particularly with respect to long-term clinical and economic outcomes. Objective To examine the five-year healthcare outcomes and all-cause costs for adults who sustain burns, according to burn severity. Methods A cost study based on a retrospective cohort of adults (≥ 14 years) admitted to any hospital in Quebec, Canada, with a burn injury between April 1, 2006, and March 30, 2017, was conducted using data from administrative databases. Follow-up ended at death or five years after the burn injury. We performed descriptive analyses of patient characteristics and of key clinical and all-cause healthcare utilization cost outcomes over five years from the provincial Ministry of Health perspective. Analyses were stratified according to burn severity. Costs are presented in 2022 CAD. Results The cohort included 6,200 individuals, of whom 39% had ≥ 20% total body surface area or full-thickness burns, 51% had < 20% total body surface area partial-thickness burns, and 10% had burns of undetermined severity. Overall, 46% were initially treated in a burn unit. The majority were male (67%), with an average age of 49 years. Patients with ≥ 20% total body surface area or full-thickness burns had a five-year mean cost of $51,865, whereas the ones with < 20% total body surface area partial-thickness burns, had a five-year mean cost of $37,097. Conclusion Only including patients treated in burn units overlooks a substantial portion of the burn population. Our study underscores heterogeneity in clinical and economic outcomes, varying according to age and burn severity.